RANCANG BANGUN SISTEM KEAMANAN DROPBOX PAKET DENGAN MENGGUNAKAN SIDIK JARI - Tiara, Nurul; Mardiono, Djoko Anwar; Toto H , Gunawan; Friadi, John (Universitas Putera Batam, 2024)
The design of this tool is to help overcome anxiety in receiving package deliveries, so that having this tool can provide a sense of security for home owners when they are not at home when the package being sent arrives. This Dropbox package is designed with several security components including a fingerprint sensor (Finger Print ZFM-20) and Keypad. Finger Print functions to open the door of the dropbox by the home owner. Apart from that, you can also open the dropbox door by using a PIN that is entered into the keypad. The keypad function is to input the last 6 digits of the homeowner's delivery receipt number after receiving the delivery receipt number. For goods delivery couriers, if the courier wants to put a package into the dropbox, the courier must enter the 6-digit receipt on the delivery package. If the receipt number entered matches the homeowner's receipt number, then the dropbox lid can be opened so the courier can enter the package. The homeowner will receive a notification when the package has arrived via SMS. The result of testing this tool is the creation of a sensory-based intelligence system that combines several sensors to control Dropbox Package access